Pembuatan Aplikasi Android Sebagai Media Pembelajaran Menarche Pada Remaja Putri Desa Kemuning Lor Kabupaten Jember - Bakhtiyar Hadi Prakoso; Veronika Vestine; Gandu Eko Julianto Suyoso; Dina Fitriyah; Surya Dewi Puspita (Indonesian Journal Publisher, 2022)
Puberty is a period of transition from childhood to adolescence. One of the signs experienced by adolescent girls is the presence of menarche. Seeing the current condition of society, many parents, especially mothers, are less than optimal in providing education for their daughters when experiencing the menarche process. In this service activity, an android application will be created that functions to help menarch education. The activity began with the application design process and socialization to young women in the village of Kemuning Lor, Jember Regency. The results of this community service activity are as many as 80% of participants feel helped by the android application. In the future, the android application that is built can be developed by increasing educational content related to menarche.